ETOS KERJA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PROSES PEMBELAJARAN DI SMAI ALMAARIF SINGOSARI - Faizun Ulurrosyad; Muhammad Afifulloh; Mohammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The work ethic of teacher is one of the main elements in the learning process, where it is urgently needed to improve the effectiveness and efficiency of the learning process in a school education. A high work ethic is an effort to improve the quality of education can be achieved, as the researchers conducted a study in SMAI Al Ma’arif Singosari. In this study, using the three instruments are: interviews, observation and documentation. The researchers also aimed to describe: 1). The work ethic of Islamic religious education teachers in the academic field, 2). The work ethic of Islamic religious education teachers in the academic field, 3). Factors supporting and work ethic of Islamic religious education teachers in improving the learning process. From the results of this study indicate that an outline of the work ethic of Islamic religious education teachers in SMAI Al Ma’arif Singosari in academic and non-academic developed through activities that reflect a high work ethic, so that in the event of Islamic religious education teachers involved and oversees.